Strengthening the Role of Teachers as Agents of Leadership Development Through Baitul Arqam: An Evaluation of The Human Resource Development Program in Sorong Regency - Sirojjuddin Sirojjuddin; Muhammad Muzaki; Budi Santoso; Solehun Solehun; Farcham Mulloh; Teguh Yuliandri Putra; Endang Gunaisah (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Baitul Arqam program is an important means of strengthening the ideological, spiritual, professional, and digital capacities of teachers within Muhammadiyah educational institutions. However, an initial needs assessment in Sorong Regency indicated that only approximately 40% of the 120 identified Muhammadiyah teachers had a good understanding of the Matan Keyakinan dan Cita-Cita Hidup Muhammadiyah (MKCH), indicating the need for more structured teacher development. This community service program aimed to strengthen teachers’ understanding of Muhammadiyah values, their role as agents of cadre development, and their professional and digital capacities. The program involved 76 teachers from 19 Muhammadiyah schools and madrasahs and was implemented using a Participatory Action Research (PAR) approach consisting of needs identification, planning, action, reflection and evaluation, and follow-up. The activities combined interactive lectures, group discussions, experiential learning, spiritual activities, Fiqh of Information, and school branding practices. Program outcomes were evaluated through pretest and posttest, participant observation, satisfaction surveys, and action plans. The results showed that the average participant score increased from 62 in the pretest to 84 in the posttest, representing an increase of 22 points or 35.48% relative to the initial score, with 68 participants (89.5%) experiencing an increase in scores. The satisfaction survey, completed by 72 participants (94.7%), produced an average score of 3.74 out of 4, indicating a very positive response. Furthermore, 100% of participants developed action plans for implementing the outcomes of the program in their respective schools. These findings indicate that the PAR-based Baitul Arqam program provided positive immediate outcomes in strengthening teachers’ understanding, engagement, and readiness for follow-up action. Continued monitoring and mentoring are recommended to assess the implementation of action plans and the longer-term impact of the program.